Analisis faktor-faktor yang mempengaruhi pendapatan industri kerajinan bambu di kabupaten bangli - Wijaya, I B Kresna; Utama, Made Suyana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 4, April 2016 (pp.385 - 429), 2016)
The role of the industrial sector aimed at strengthening the the economic sector nasional and mutual support between sectors, boost the national economy, provide employment in order to reduce proverty and community development is also expected to boost per capita growth. Technology is a whole means toprovide goods for the survival and comfort of human life. With the help of capital intensive technology in the form of machines, then the process product company will more easily and quickly. Technology as a tool can be utilized in the production process, so that efforts to increase sales can be optimally performed and revenue increased. The purpose of this study was to determine whether the raw materials, capital, labor, and technology influence simultaneously and partially on operating revenues of bamboo crafts in Bangli regency. The research design for this study is the use of regression with moderating variable. Location or scope of this area of research conducted in Bangli regency. Object of this research is the object of bamboo handicraft industry in Bangli regency. Source of data used is primary data. The results showed that raw materials and significant positive effect on the income of bamboo handicraft business in Bangli regency. Modal positive and significant impact on the income of bamboo handicraft business in Bangli regency. Labor and significant positive effect on the income of bamboo handicraft business in Bangli regency. Technology able to moderate the influence of raw materials, capital and labor to the revenue bamboo handicraft in Bangli regency.
Keywords: Raw Materials, Capital, Labor, Technology, Earnings, Bamboo